The effect of gum-chewing on relieving motion sickness - GOTO, Takeshi; SUZUKI, Yoshihisa; SATO, Yoshinori; KOBAYASHI, Takashi; KUDO, Shozo; TAKIGUCHI, Toshio (Journal of Japanese Society for Mastication Science and Health Promotion, 1997)
It is known that gum-chewing has a lot of effects, for example, to prevent from falling into drowsiness, to remove bad breath, to reduce dental plaque, and so on. Also we guess gum-chewing has the effect of relieving motion sickness. So, we tried to make a comparative study of the effects of gum-chewing for subjects easy to feel motion sickness by using six-axis motion base. We made experiments for every subject in three cases. In two cases, it chewed two kinds of gum one by one, and in one case, it chewed none. As it was expected that there existed some order effect, we divide subjects into 4 groups with different orders ofcases. We apply the analysis of variance for two-way layout to the measured values of the level of heavy head, heavy stomach and nausea. As a result, it is seen that gum-chewing has the effects of relieving motion sickness. We used two kinds of chewing gum, mint flavor and fruit one, but we cannot find the difference of the effects between them.